On the time dependent mathematical model of ateroma plaque formation - Cilla, Myriam; Peña, Estefanía; Martínez, Miguel Ángel (Jornada de Jóvenes Investigadores del I3A, 2014)
A mathematical model to reproduce the atheroma plaque growth is presented. This model employs the Navier-Stokes equations and Darcy’s law for fluid dynamics, convection-diffusion-reaction equations for modeling the mass balance in the lumen and intima, and the Kedem-Katchalsky equations for the interfacial coupling at membranes, i.e., endothelium.